2009
DOI: 10.1074/jbc.m807698200
|View full text |Cite
|
Sign up to set email alerts
|

CD96 Interaction with CD155 via Its First Ig-like Domain Is Modulated by Alternative Splicing or Mutations in Distal Ig-like Domains

Abstract: The adhesion receptor CD96 (TACTILE) is a transmembrane glycoprotein possessing three extracellular immunoglobulinlike domains. Among peripheral blood cells, CD96 is expressed on T cells as well as NK cells and a subpopulation of B cells. A possible function of this receptor in NK cell-mediated killing activities was suggested recently. Moreover, CD96 was described as a tumor marker for T-cell acute lymphoblastic leukemia and acute myeloid leukemia. CD96 binds to CD155 (poliovirus receptor) and nectin-1, an ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 24 publications
1
87
0
Order By: Relevance
“…Recently, CD96 was identifi ed, with TIGIT , as amongst the top 20 T cell-associated genes expressed in a screen of human lung squamous cell carcinoma samples ( 38 ). Human CD96 has been previously reported to play a role in facilitating NK-cell adhesion/cytotoxicity against CD155-expressing tumor cells ( 33,46 ). Whether anti-human CD96 mAbs can promote NK-cell/T-cell function remains to be established.…”
Section: Research Articlementioning
confidence: 99%
“…Recently, CD96 was identifi ed, with TIGIT , as amongst the top 20 T cell-associated genes expressed in a screen of human lung squamous cell carcinoma samples ( 38 ). Human CD96 has been previously reported to play a role in facilitating NK-cell adhesion/cytotoxicity against CD155-expressing tumor cells ( 33,46 ). Whether anti-human CD96 mAbs can promote NK-cell/T-cell function remains to be established.…”
Section: Research Articlementioning
confidence: 99%
“…CD155 belongs to the nectins, a family of Ig-like transmembrane proteins (21). All known physiological and pathogenic functions of CD155 are mediated via its outermost V-like domain harboring the docking epitopes for its known ligands: nectin-3, vitronectin, CD226, CD96, and poliovirus (22)(23)(24)(25)(26)(27)(28)(29). CD155 is involved in the establishment of adherens junctions between endothelial and epithelial cells (21) and was shown to influence cell motility, migration, and proliferation (30,31).…”
mentioning
confidence: 99%
“…25 Prior studies of AS identified several genes mis-spliced in AML patients, including AML1, Gfi1b, CD96, survivin-2B, and GSK3beta. 8,15,21,[26][27][28][29] In our previous study, we used exon arrays to compare genome-wide gene-splicing events in AML vs normal CD34 1 cells and observed widespread differences. 30 Among the most frequently mis-spliced genes in AML patients were NOTCH2 and FLT3, and here we describe these events in detail.…”
Section: Introductionmentioning
confidence: 99%